Stock Price Synchronicity And Institutional Ownership: The Role Of Sustainability Reporting, Political Connection, And Leverage - Muhamad Haidar Feryan; Muhammad Nuryatno Amin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research study is aimed to evaluate how institutional ownership affects the degree of correlation among stock prices, as well as the influence of sustainability reporting, political connections, and leverage. The study takes sample data from companies that were on the LQ45 index at the end of the year, or December 31, for the years 2019–2022 using purposive sampling method. Hypothesis testing uses a multiple linear regression analysis model in the form of a moderated regression analysis (MRA) to test moderator variables. The findings indicated that leverage has negative effect on stock price synchronicity, while neither sustainability reporting nor political connections influenced stock price synchronicity. Institutional ownership as a moderating variable is able to strengthen the negative influence of leverage on stock price synchronicity, On the other hand, the presence of institutional ownership does not have an ability to impact the correlation between sustainability reporting and political relationships on stock price synchronicity